Relative Importance of Mode of Administration in Treatment Preferences among Plaque Psoriasis Patients in the United States - Steven R. Feldman; Anders Holmen Moeller; Sandra T. Erntoft Idemyr; Juan Marcos González (Journal of Health Economics and Outcomes Research)
**Background:** Some aspects of psoriasis treatments can negatively influence patients’ quality of life. There is evidence from previous preference-elicitation research in psoriasis that administration characteristics are at least as important as treatment outcomes to patients.